Systematic evaluation of urinary formic acid as a new potential biomarker for Alzheimer’s disease - Wang, Yifan; Wang, Ying; Zhu, Jinhang; Guan, Yihui; Xie, Fang; Cai, Xiao; Deng, Jiale; Wei, Yan; He, Rongqiao; Fang, Zhuo; Guo, Qihao (Frontiers in Aging Neuroscience, 2022)
Introduction The accumulation of endogenous formaldehyde is considered a pathogenic factor in Alzheimer’s disease (AD). The purpose of this study was to investigate the relationship between urinary formic acid and plasma biomarkers in AD. Materials and methods Five hundred and seventy-four participants were divided into five groups according to their diagnosis: 71 with normal cognitive (NC), 101 with subjective cognitive decline (SCD), 131 with cognitive impairment without mild cognitive impairment (CINM), 158 with mild cognitive impairment (MCI), and 113 with AD. Results With the progression of the disease, urinary formic acid levels showed an overall upward trend. Urinary formic acid was significantly correlated with Mini-Mental State Examination (MMSE) scores, the Chinese version of Addenbrooke’s Cognitive Examination III (ACE-III) scores, and Montreal Cognitive Assessment-Basic (MoCA-B) time. The areas under the receiver operating characteristic curves (AUC) of urinary formic acid in distinguishing NC from AD was 0.797, which was similar to that of plasma neurofilament light chain (NfL; AUC = 0.768) and better than other plasma biomarkers (Aβ40, Aβ42, Aβ42/Aβ40, T-tau, P-tau181, and P-tau181/T-tau). We also found that using urinary formic acid and formaldehyde levels could improve the accuracy of using plasma biomarkers to determine AD disease stage. Discussion Our study revealed the possibility of urinary formic acid as a potential novel biomarker for the early diagnosis of AD.